Facing Trajectories from School to Work
XII, 394 p. 15 illus.
Keywords: This book promotes a radical alternative impact on youth policy in Europe to overcome the situation of vulnerability and discrimination of a growing number of youngsters in their transition from school to work. It follows a Human Development perspective in using the Capability Approach (CA) as analytical and methodological guiding tool to improve the social conditions of the most socially vulnerable young people in European societies. The mission of the interdisciplinary authors is to expand the actual chances of the young to actively shape their lives in a way they have reason to choose and value. This book is based on the research of the EU Collaborative Project “Making Capabilities Work” (WorkAble), funded by the EU within the Seventh Framework Programme. It is the first empirical project to pursue a justice theory perspective on a European level. It also contributes to a fundamental change in the currently mostly insufficient attempts within the human capital approach to use the labour market to ensure desired lifestyle forms and a secure income for vulnerable youth.